The paper caper - Carlisle, Kate, 1951- (Carlisle, Kate, 1951- Bibliophile mystery, 2022)
"San Francisco book-restoration expert Brooklyn Wainwright is back with an intriguing new mystery in the New York Times bestselling Bibliophile Mystery series. Joseph Cabot is a very popular wealthy San Franciscan who owns the main newspaper in town, as well as radio stations and TV. Years ago, Brooklyn's husband Derek and his security team rescued Joseph from an assassination attempt and now the man and his wife are friendly with Derek and Brooklyn. The friendship is helped along by the fact that Joseph is a big book lover and contributes lavishly to the Covington Library. His favorite author is Mark Twain (another newspaperman) and he's underwritten the first annual Mark Twain Festival at the Covington. As part of the festival activities, Brooklyn will spend a few hours every day at the Library, giving demonstrations of her work at re-binding an old copy of The Prince and the Pauper. There will be events all week, all around town, celebrating the time Twain spent in the city. But the biggest event is being run by Joseph's newspaper: a citywide contest based on The Prince and The Pauper--they want to find someone who looks like Joseph! The two men will trade places for a week as part of a huge publicity campaign to raise money for the Covington Library. But the fun turns frantic when a murder occurs right before Brooklyn's eyes! Now Brooklyn and Derek will have to chase clues all over their beloved city to solve the murder before another death becomes front-page news"--